Modifikasi Alat Monitoring Pada Tangki Pengaduk Promol Menggunakan Nextion Display Berbasis Arduino Mega - Putra, Arya Dama; Prasetyo, Henry (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
Technological developments in the world, especially in Indonesia, have increased quite rapidly. In its development, new items emerged with all kinds of functions. Likewise with industries that are closely related to technology. In industrial material processing, especially in the manufacturing world, optimal measurements are always needed to measure the accuracy of the required specs. In this study, the authors used an ultrasonic sensor with the aim of measuring the water level in the promol stirrer tank. In addition, the Nextion Display is used as a user interface to display water level information. Nextion Display provides an easy-to-read and interactive visual display. Users can see the water level in the form of numbers or graphs, and receive notifications when the water level reaches a specified limit. To implement this monitoring tool, ultrasonic sensors and Nextion Displays are connected to a microcontroller or other electronic device that has serial communication capabilities. The water level data obtained from the ultrasonic sensor is sent to the microcontroller, and then displayed on the Nextion Display.